Delays in the diagnosis and treatment of bone and joint tuberculosis in the United Kingdom. (January 2018) - Broderick, C.; Hopkins, S.; Mack, D. J. F.; Aston, W.; Pollock, R.; Skinner, J. A.; Warren, S.
Abstract : Aims: Tuberculosis (TB) infection of bones and joints accounts for 6.7% of TB cases in England, and is associated with significant morbidity and disability. Public Health England reports that patients with TB experience delays in diagnosis and treatment. Our aims were to determine the demographics, presentation and investigation of patients with a TB infection of bones and joints, to help doctors assessing potential cases and to identify avoidable delays. Patients and Methods: This was a retrospective observational study of all adults with positive TB cultures on specimens taken at a tertiary orthopaedic centre between June 2012 and May 2014. A laboratory information system search identified the patients. The demographics, clinical presentation, radiology, histopathology and key clinical dates were obtained from medical records. Results: A total of 31 adult patients were identified. Their median age was 37 years (interquartile range (IQR): 29 to 53); 21 (68%) were male; 89% were migrants. The main sites affected were joints (10, 32%), the spine (8, 26%) and long bones (6, 19%); 8 (26%) had multifocal disease. The most common presenting symptoms were pain (29/31, 94%) and swelling (26/28, 93%). 'Typical' symptoms of TB, such as fever, sweats and weight loss, were uncommon. Patients waited a median of seven months (IQR 3 to 13.5) between the onset of symptoms and referral to the tertiary centre and 2.3 months (IQR 1.6 to 3.4.)) between referral and starting treatment. Radiology suggested TB in 26 (84%), but in seven patients (23%) the initial biopsy specimens were not sent for mycobacterial culture, necessitating a second biopsy. Rapid Polymerase Chain Reaction-based testing for TB using Xpert MTB/RIF was performed in five patients; 4 (80%) tested positive for TB. These patients had a reduced time between the diagnostic biopsy and starting treatment than those whose samples were not tested (median eight days versus 36 days, p = 0.016). Conclusion: Patients with bone and joint TB experience delays in diagnosis and treatment, some of which are avoidable. Maintaining a high index of clinical suspicion and sending specimens for mycobacterial culture are crucial to avoid missing cases. Rapid diagnostic tests reduce delays and should be performed on patients with radiological features of TB. Cite this article: Bone Joint J 2018;100-B:119–24.